A systems analysis ritique of sport-science research - McLean, S.; Kerhervé, H. A.; Stevens, N.; Salmon, P. M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The broad aim of sport-science research is to enhance the performance of coaches and athletes. Despite decades of such research, it is well documented that sport-science research lacks empirical evidence, and critics have questioned its scientific methods. Moreover, many have pointed to a research-practice gap, whereby the work undertaken by researchers is not readily applied by practitioners. The aim of this study was to use a systems thinking analysis method, causal loop diagrams, to understand the systemic issues that interact to influence the quality of sport-science research.